Risk-averse behaviour in emerging markets: the role of economic indicators, bank characteristics and developed markets - Ooi, Kok Loang, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to examine the impact of economic indicators and bank characteristics on investors' risk-averse behaviour in emerging countries. It further analyses the influence of the developed markets on the risk-averse behaviour of the emerging markets. This study specifically explores the tendency of risk-averse behaviour among investors, as described in the Prospect theory. Using India, Indonesia, Malaysia and China as the sample countries over the 2010-2021 period, this study employs panel data regression with excess return, three-factor alpha, five-factor alpha and six-factor alpha models for robustness testing. The results showed that the economic indicators, namely IMF growth forecast, GDP growth rate, and real interest rate significantly impact risk-averse behaviour. Bank characteristic of non-performing loans also explains risk-averse behaviour. In addition, the US as a developed market is significantly correlated with investors' behaviours in emerging markets. The results of the quantile regression showed that Malaysian investors have the highest tendency towards risk-averse behaviour, followed by Indonesia, China and India. This study may assist regulators, policymakers and practitioners in determining the tendency of risk-averse behaviour. The respective parties should regularly monitor, control and regulate investors' risk aversion as the contagion effect of extreme irrational behaviour can lead to market crash and financial crisis.